Rodzina jako środowisko wychowawcze dziecka z deficytami rozwoju. Społeczna rola ojca jako opiekuna i facylitatora - Minczakiewicz, Elżbieta Maria (Karkonoska Państwowa Szkoła Wyższa, 2011)
The prepared text is a personal reflection on the structure and meaning of social relationships in contemporary families early twenty-first century, with particular emphasis on families with a child with symptoms of physical or intellectual disability. The major emphasis has been placed there for his father's social role, which in the social constellation which is the family, is sometimes not very clear, sometimes even marginalized, and most interesting families we underestimated the extent that it actually deserves. For drawing generalizations based on the assumed problems accumulated empirical material gathered through observation and interview about 500 families involved. For providing intelligence were both parents of a disabled child, as well as his siblings and other relatives. This properly collated and developedaccordance with the suggestion of interested participants in the seminars for parents raising a child with disabilities development, helped to expose and develop a 12-theoretical models of structural and relational families, preferring certain attitudes towards the disabled child and his upbringing. Our results for which I made in the development, servedme for a plot to show the verymuch appreciated and is vital in the life of a disabled child, his father's social role as a carer, friend and facilitator.
Keywords: rodzina; edukacja; niepełnosprawni; deficyty; rozwój; ojcostwo; macierzyństwo; relacje rodzinne; role społeczne